Paget's disease of the breast - Toledo Correa, Nancy (Cirugía del Uruguay, 2021)
Histopathological characteristics of the disease first described by Paget in 1874 are: The presence of Paget's large, clear, intra-epidermic cells in the nipple skin and areola; these are malignant, neoplasic cells. Atypical intraduct epitheiial proliferation in the terminal ducts of the nipple, which is also carcinomatose Finally --subject io the time the patient has suffered from this condition- a deep mammary carcinoma. According to sorne, Paget's cell is a consequence of cancer in the nipple ducts and has invaded the epidermis in the area. According to others, this is an autoctonous epidermic cell and consequently .coexists with the duct lesion and, eventually, with the deep · mammary. cancer. The latter theory is predominant. The skin lesion is really an "in situ" or intraepithelial cancinoma.